Peningkatan Kemampuan Menggunakan Huruf Kapital pada Mata Pelajaran Bahasa Indonesia melalui Metode Pemberian Tugas Siswa Kelas VI UPTD SD Negeri 3 Barru - Desy Ayu Andhira; Reski Amalia; Hikma Rajab (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This research aims to determine the increase in the ability to use capital letters in class VI students by Applying The Assignment method in Indonesian language learning. This research is classroom action research, namely research carried out in the classroom as an effort to examine, analyze and critically a teacher's learning plan, teacher interactions with students, and how students interact in class. Increased implementation of the learning process in class from cycle I with an average score of 62,37% with the category not having reached the predetermined success criteria, and in cycle II with a score reaching 84,04%. This means that the research indicators have been achieved and there is no need to continue in the next cycle.